Feature articles : LeRoy Neiman and the art of network sports television - Vogan, Travis (American art, 2016)
Famous for his vibrant and splashy paintings of the sporting life and illustrations for Playboy magazine, LeRoy Neiman (19212012) at one time stood among the United States' most popular and wealthiest artists. He was alsoin large part because of his visibility, fortune, and engagement with mass cultural subject matter--almost universally dismissed by critics and curators. Neiman's regular appearances on the stereotypically lowbrow medium of television, in particular the American Broadcasting Company's "Wide World of Sports" and coverage of the 1972 and 1976 Summer Olympic Games, intensified his fame, prosperity, and disavowal. ABC Sports president Roone Arledge used the conspicuous, macho, and media savvy artist to augment his humanized, "up close and personal" approach to producing sports TV. Histories of art and television have almost entirely ignored the intersections between these media. The little scholarship that does examine art and television's intersections overlooks Neiman's high profile appearances. However, these appearances demonstrate how network sports television helped to create one of the United States' most famous and polarizing artists. They also show how Neiman contributed to ABC's codification of sports TV's creative and commercial ambitions and reflected the cultural logic informing the kinds of art and artists welcome on it. OA